Modeling and verification of Industrial Microservice Architecture Based on Formal Methods - Meng, Xiangxi; Duan, Xiangyu; Tao, Wei; Luan, Yan; Zhang, Juanjuan; Wu, Donghan (Chinese Automation Congress (Online), 2021)
The microservice architecture has become the mainstream technology of industrial applications development in the Industrial Internet Platform. The test and verification of microservice architecture is the guarantee of industrial application credibility. By analyzing the microservice architecture of industrial applications, this paper proposes an application interface tree model method, which is used to model and verify the microservice architecture. Application Interface Tree supports characterization of the attributes and interactions of microservices, on which the static and dynamic models of microservice architecture can be established respectively. The relationship between microservices and running environment can be expressed by static model, while the dynamic model reflects the interface invocation between microservices. The correctness of the interaction between the model interfaces can be defined by the state transition diagram. Then the correctness of the microservice architecture can be proved by the model detection algorithm. In this paper, an industrial application is modeled, and the Application Interface Tree Model is used for model detection. The results verify the effectiveness of this method.